2015
DOI: 10.1016/j.seizure.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Temporal current-source of spikes suggests initial treatment failure in childhood absence epilepsy

Abstract: Initial AED failure was associated with temporal involvement in the CSD of CAE patients. This electrophysiological information may be helpful in clinical practice by estimating the efficacy of initial AED treatment in AED-naïve CAE patients in advance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…This concerned both patients with temporal seizures and those with JME. Of note is that symmetrical patterns were not observed in patients with absence seizures, where the discharges are usually bilateral, symmetric, and synchronous [28,29]. Apart from this, we found no significant correlation between particular patterns and the type of epilepsy.…”
Section: Results Discussioncontrasting
confidence: 69%
“…This concerned both patients with temporal seizures and those with JME. Of note is that symmetrical patterns were not observed in patients with absence seizures, where the discharges are usually bilateral, symmetric, and synchronous [28,29]. Apart from this, we found no significant correlation between particular patterns and the type of epilepsy.…”
Section: Results Discussioncontrasting
confidence: 69%
“…In addition, Yeom et al explored the prognostic significance of the localization of the GSWD generator in CAE patients [ 73 ], following previous functional magnetic resonance imaging studies which highlighted that cortical GSWD generators were associated with a less satisfactory seizure control compared with “classical” thalamic sources [ 74 ]. The researchers used exact low-resolution brain electromagnetic tomography analysis to examine current sources of averaged GSWDs and found a significantly higher involvement of the temporal lobe in drug-resistant CAE patients compared with ASM-responsive ones, in line with previous functional magnetic resonance findings.…”
Section: The Emerging Role Of Advanced Eeg Analysis In the Identifica...mentioning
confidence: 99%
“…» The composition of the epileptic network may influence drug responsiveness Szaflarski et al [99] reported that VPA-resistant and VPA-responsive patients may have different spike-wave generators and that these differences in generalized seizures may be the reason for different responses to VPA. Yeom et al [100] found that an initial ASM failure was associated with temporal involvement in the current source distribution of CAE patients. This electrophysiological information, also called "pharmaco-EEG," may be helpful in clinical practice by enabling estimation in advance of the efficacy of initial ASM treatment in ASM-naïve CAE patients.…”
Section: Precision Therapymentioning
confidence: 99%